A disaster typology towards informing humanitarian relief supply chain design. Issue 1 (30th April 2019) - Mackay, Jonathon; Munoz, Albert; Pepper, Matthew
Abstract : Purpose: The purpose of this paper is to construct a typology of a disaster that informs humanitarian-relief supply chain (HRSC) design across the stages of disaster relief. Design/methodology/approach: In addition to an interdisciplinary review of pertinent literature, this paper utilises a typology construction method to propose theoretically and methodologically sound dimensions of disasters. Findings: Whilst semantic arguments surrounding the concept of a "disaster" are ongoing, the authors propose three typologies based upon six dimensions that serve as interdependent variables informing resultant HRSC design considerations. These are speed of onset, time horizon, spatial considerations, affected population needs, perceived probability of occurrence and perceived magnitude of consequence. These combinational and independent relationships of the variables offer insight into key HRSC design-making considerations. Research limitations/implications: The study improves conceptual knowledge of disasters, distilling the concept to only the dimensions applicable to HRSC design, omitting other applications. The typologies provide empirical cell types based on extant literature, but do not apply the models towards new or future phenomena. Practical implications: This paper provides HRSC practitioners with normative guidance through a more targeted approach to disaster relief, with a focus on the impacted system and resulting interactions' correspondence to HRSC design. Originality/value: This paper provides three typological models of disasters uniquely constructed for HRSC design across the various stages of disaster relief.